Cost-benefit analysis of conserving marine biodiversity in the Sagay Marine Reserve, Sagay City, Negros Occidental. - Guanzon, Teresa Ira Maris Padilla
Studies about Marine Reserves are important to see if it does pay to conserve and at the same time arouse more participation from the government, community and academe. This study compared the costs and benefits of the Sagay Marine Reserve (SMR), the second largest marine reserve in Philippines covering 32,000 hectares, found in Sagay City, Negros Occidental in the year 2004. The costs and benefits were determined through primary (through key informants and survey respondents) and secondary data from different offices of the city most especially the City Environment and Natural Resources - Sagay Marine Reserve (CENRO-SMR) Office. These costs were divided into fixed cost, variable cost (which includes maintenance, operating and labor costs) and opportunity cost. The total cost of the Sagay marine Reserve is Php 5, 143, 511.30. The benefits were divided into Direct Use Values, Indirect Use Values and Non-Use Value. The Direct Use Values include revenues from ahrvesting of shells, sea cucumber, seagrass and fish, permits and licenses and fines. The Indirect Use Values include the carbon sequestration value and shoreline protection value of mangroves and the coastal protection, waste treatment and food production and biological control values of coral reefs. The Non-Use Value only included the conservation value of the SMR based on Contigent Valuation Method (CVM). the mean willingness to pay (WTP) of the people of Sagay is Php 90.00 using the Turnbull formula. The Social WTP or the conservation value is Php 1,294,650.00. Through a regression analysis using the software Gretl, it was found that the independent variables bid price, knowledge level about the Sagay Marine Reserve and sex were highly significant and age was very significant. The bid price also has an inverse relationship to the WTP reply meaning that the lower the bid price the higher the willingness to pay of people. On the other hand, the more people know about the SMR, the more they would be willing to pay. Males were more likely to say yes compared to females since 66.2 percent of the respondents were males. It was also found out that he younger the respondent, the more willing to pay he would be. The total benefit from the SMR is 308, 999, 190.50. This value is also trhe economic value of the SMR. The economic value per hectare of the SMR is Php 9, 656.22. This value is underestimated since other biological and ecological vlues of other resources in the SMR were not included as well as other non-use values. The net present value of the SMR over 20 years with varying interest rates of 5 percent, 10 percent, 12 percent and 20 percent was positive for all interest rates. This shows that the SMR is beneficial. The benefit cost ratio is 59.30 is to 1. This means that for every peso invested, the city of Sagay gets Php 59.30 in return. Thus, it does pay to conserve the resources in the Sagay Marine Reserve. A sensitivity analysis was also performed using only 25 percent of the Indirect Use Values from Coral Reefs. This lowered the benefits to Php 81, 734,490.52, but the net present value after 20 years at varying interest rates was still positive. The benefit cost ratio also decreased to 15.89. However, this shows that it still pays to conserve. Based on these results, the government should continue the operation of the Sagay Marine Reserve and should develop strategies to improve the operation of the SMR with the help of multi-sectoral groups most especially the community and all of the government offices.